DEVELOPING CHILDREN’S CREATIVITY THROUGH FINE ARTS AND HANDICRAFT BASED ON FOLK PEDAGOGY (TAMADDUN NURI JURNALI, 2025)
This article explores the importance of developing creativity in children through visual arts and handcrafts based on folk pedagogy. It examines the significance of folk pedagogy in shaping creative thinking and practical skills in students and its integration into the educational process. The article analyzes how visual arts and handcrafts contribute to students' aesthetic development, the formation of independent thinking, and the enhancement of creative approaches. It highlights the role of folk pedagogical values and traditional teaching methods in guiding students to express their individual creativity through practical activities.